2000
DOI: 10.1029/2000jb900210
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional seismic structure and physical properties of the crust and shallow mantle beneath the East Pacific Rise at 9°30'N

Abstract: Abstract. The seismic structure of the crust and shallow mantle beneath the East Pacific Rise near 9ø30'N is imaged by inverting P wave travel time data. Our tomographic results constrain for the first time the three-dimensional structure of the lower crust in this region and allow us to compare it to shallow crustal and mantle structure. The seismic structure is characterized by a low-velocity volume (LVV) that extends from 1.2 km depth below the seafloor into the mantle. The cross-axis width of the LVV is na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
374
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(408 citation statements)
references
References 74 publications
30
374
4
Order By: Relevance
“…6d). We note that Maclennan et al's hydrothermal models employed adjustable heat extraction rates to match the thermal structures derived from the 2-D seismic tomography in Dunn et al (2000). Instead, using permeability to explicitly regulate porous hydrothermal flows in the thermal modeling, Cherkaoui et al (2003) suggested that a permeability of ∼4 × 10 −14 m 2 or greater is required to reproduce the thermal structure of Dunn et al (2000).…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 99%
See 2 more Smart Citations
“…6d). We note that Maclennan et al's hydrothermal models employed adjustable heat extraction rates to match the thermal structures derived from the 2-D seismic tomography in Dunn et al (2000). Instead, using permeability to explicitly regulate porous hydrothermal flows in the thermal modeling, Cherkaoui et al (2003) suggested that a permeability of ∼4 × 10 −14 m 2 or greater is required to reproduce the thermal structure of Dunn et al (2000).…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 99%
“…A schematic illustration of crustal formation beneath fast-spreading mid-ocean ridges. Thin white curves are isotherms from Dunn et al (2000) showing the thermal structure derived from seismic tomography assuming the effects of anharmonicity and anelasticity. Blue curves with arrows indicate hydrothermal circulations near the ridge axis for efficiently removing heat across the entire crust.…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…An axial magma chamber (AMC) has been detected -1.2-2 km beneath the axis in the surveyed area and the continuity of the AMC reflector is disrupted at several locations along-axis (e.g., at 90 17'N and 90 53'N), suggesting possible individual magma systems [Detrick et al, 1987;Kent et al, 1993; Vera and Diebold, 1994; Toomey et al, 1994] or locally enhanced mantle melt supply [Dunn et al, 2000]. Above the AMC, in the upper crust, the reflection from the base of seismic Layer 2A is observed to increase in depth from -0.2 km at the axis to -0.5 km at 1-2 km off axis [Christeson et al, 1992;Harding et al, 1993;.…”
Section: Regional Settingmentioning
confidence: 99%
“…The overlapping spreading center (OSC) at 9103′N EPR presents an ideal opportunity for studying the relationships between volcanism and magmatism because the subsurface melt distribution and seafloor morphology have recently been well-characterized in a number of geophysical and geological studies (e.g., Bazin et al,a low velocity anomaly interpreted as melt in the uppermost mantle extending across the OSC, with the lowest velocities centered beneath the eastern limb (Dunn et al, 2000;Toomey et al, 2007), melt accumulation in the overlying crust (Singh et al, 2006), and a mid-crustal mush zone at the northern end of the overlap basin at~9108′N (Bazin et al, 2003;Crawford and Webb, 2002). In addition, a 3-D seismic reflection study reveals a~4 km wide, upper-crustal melt sill beneath the eastern limb that extends westward into the northern portion of the overlap basin (Kent et al, 2000).…”
Section: Introductionmentioning
confidence: 99%